Future Research and Trends in Ultra-Wideband Indoor Tag Localization - Gita Indah Hapsari; Rendy Munadi; Bayu Erfianto; Indrarini Dyah Irawati (IEEE Access)
Ultra-wideband (UWB) signals are widely used for indoor tag localization because of their high accuracy, wide bandwidth, and low power consumption. The diversity and breadth of research in the field of UWB-indoor tag localization can be confusing for new researchers to determine how this research has progressed. The way to determine the trend and research opportunities in UWB indoor tag localization is to read recent papers. However, no one has reviewed the Systematic Mapping Study (SMS) and Systematic Literature Review (SLR) methods. SMS is a quantitative mapping method for identifying, categorizing, and analyzing existing literature relevant to a certain research topic. SLR is a qualitative method for collecting and critically analyzing multiple research studies or papers through a systematic process. It aims to synthesize the findings of these studies and conclude the state of the art on the topic. This paper reviews the recent UWB indoor tag localization study using the SMS and SLR methods. The reviews include demographics of recent study, topic areas of indoor tag localization from 2017-2023, UWB indoor tag localization research trends, issues, metrics, and opportunities for future research. Each optimized metric related to different issues is represented in the form of a taxonomy for easy understanding and is explained in detail in this paper. Several promising future research opportunities are described in this paper to provide insights to other researchers in this field.